Analisis Kebisingan dan Getaran Mekanis Pengoperasian Mesin Pemipil Jagung pada Kelompok Tani Balagana - Amalia, Sri Yeli; Jamaluddin, Jamaluddin; Rauf, Reski Febyanti (Agricultural Technology Education Study Program, 2024)
Mechanical shelling is by using a corn sheller machine. Where the use of a corn sheller machine produces sounds and vibrations that cause discomfort to the operator. This study aims to analyze the mechanical noise and vibration of the operation of the corn sheller machine at the Balagana Farmers Group. The research method uses an experimental approach, with descriptive data representation in the form of tables and graphs.. The resulting data is primary data. Observation parameters used in this study were noise and vibration. The results showed that the noise level of the corn sheller machine without load at a height of 120 cm obtained a noise level of 98-104.5 dB and at a height of 150 cm the noise level was 97.5-104.5 dB exceeding the NAB (>85 dB SNI). The noise level of the corn sheller machine with a load at a height of 120 cm obtained a noise level of 112.5-119.5 dB and at a height of 150 cm, namely 112-119.5 dB exceeding the NAB (>85 dB SNI). The mechanical vibration level of the corn sheller machine which was carried out at three measurement points was obtained on the machine floor of 5.1 m/s2, the medium vibration level on the upper operator floor was 3.1 m/s2 and the lowest vibration on the lower operator floor was 1.5 m /s2 is below NAV (<6 m/s2).